Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China - Tan, Ke (PhytoKeys, 2019)
Abstract. Hiptage is an Asia-endemic genus of Malpighiaceae currently placed in the tetrapteroid clade, representing one of the seven inter-continent dispersions from New to Old World. A molecular phylogeny based on sequences of the internal transcribed spacer (ITS) region was recovered for the first time for the genus. Our results showed that the most recent common ancestor of Hiptage probably originated in the South Indo-China Peninsula and diversified in this region. Based on phylogenetic evidence and relevant morphological traits, we propose a new species; Hiptage incurvatum is characterised by mericarps with arcuate anterior lateral wings, two large glands on the dorsal sepals, and small glands on the remaining sepals. The new species is from Mt. Cangshan, Dali City (25°35'N, 100°02'E) in North Yunnan, Southwest China and is notable for its occurrence at high altitude, 1400 m (the highest distribution currently known for the genus). The implications of this unusual species for the dispersal and evolution of the genus are discussed.